Improved Dynamic Spectrum and Traffic Management Model Based on Demand Response and Heterogeneous Incentives with Perfect Substitute Utility Function - Puspita, Fitri Maya; Octarina, Sisca; Yunita; Ramadhany, Adinda Putri; Yuliza, Evi (Science and Technology Indonesia, 2025)
The purpose of this research is to design and optimize a demand response based-selfish user Cloud Radio Access Network (C-RAN) model to demonstrate with a narrow-minded client utilizing three financing plans specifically level charge, usage-based, and two-part tariff. The Traffic data is classified into incoming data and outgoing data, obtained from a local server in Palembang. The optimal solution is obtained by determining the decision variables and parameters used in each case for all models, compiling improved C-RAN models as many as 2 models, namely model I, and model II, and then determining the optimal solution and sensitivity analysis using LINGO 13.0 software. The most optimal solution is obtained from model II with a flat-fee scheme in case 1 of IDR 3299.7/kbps with 45 iterations. The results of the sensitivity analysis is on the variables ak,m that allows the increase and decrease in the objective function coefficient. At the same time, the value 0 will be constant.